Measurement of Interferon Gamma Concentration Using an Electrochemical Immunosensor. Issue 5 (22nd January 2016) - Wang, Yun; Mazurek, Gerald H.; Alocilja, Evangelyn C.
Abstract : Interferon gamma (IFN-γ) plays an important role in immune responses in a variety of infections and diseases. The measurement of IFN-γ concentration can facilitate disease diagnosis. In this study, measurement of IFN-γ concentration using a nanoparticle-based electrochemical immunosensor is reported. IFN-γ was captured by antibody-functionalized magnetic nanoparticles (MNPs) and labeled with gold nanoparticles (AuNPs) conjugated with a second anti-IFN-γ antibody and multiple cadmium sulfide nanoparticles (CdS-NPs), thus forming the MNP-IFN-γ-Au-CdS complex. After magnetic separation, the complex was resuspended in a dilute nitric acid solution, mixed with bismuth, and added to a screen-printed carbon electrode (SPCE) chip. The electrochemical signal from the CdS-NPs was measured using square wave anodic stripping voltammetry (SWASV). Maximum current at −0.87 V was linearly associated with IFN-γ concentration over the range of 0.01 to 1 IU/ml. Measurement of IFN-γ concentration with this immunosensor required about 1 hour. These characteristics suggest that, with optimization, this immunosensor may have clinical utility.